Distribution Automation : An Opportunity to Improve Reliability and Quality - Oguah, Samuel (World Bank, Washington, DC, 2016)
The control systems of today’s smart power-distribution grids have evolved significantly. Such systems improve system reliability by reducing the frequency and duration of outages. They also optimize asset utilization and increase power quality. But the scale of automation and the ultimate configuration of the system need to be considered carefully with each client. The decision to proceed must be based on a sound economic evaluation; it cannot simply echo the mantra of automation.